Image-guided percutaneous mechanical disc decompression for herniated discs: a technical note - Liguori, Alessandro; Pandolfi, Marco; Gurgitano, Martina; Arrichiello, Antonio; Angileri, Salvatore Alessio; Di Meglio, Letizia; Ierardi , Anna Maria; Paolucci, Aldo; Galli, Federica; Stellato , Elvira; Carrafiello, Gianpaolo (Acta Biomedica Atenei Parmensis, 2020)
Interventional radiology plays a key role in the treatment of symptomatic herniations of intervertebral discs. Through image-guided techniques, it is possible to use minimally invasive procedures with a percutaneous approach that are usually proposed before classic surgery. Thanks to imaging guidance, it is possible to significantly increase accuracy and decrease complication rates. The pivotal principle of these mini-invasive techniques is to remove a small amount of volume of the nucleus of the intervertebral disc which results in a significant reduction in intradiscal pressure; allowing for a consequent reduction in compression of the nervous structures that generate spinal pain. However, it must be considered that this type of treatment is only addressed to contained disc herniations previously diagnosed with a suitable neuroimaging examination. There are different types of treatment using a variety of chemical, thermal or mechanical processes that result in partial removal of the nucleus pulposus. The purpose of this technical note is to illustrate mechanical disc decompression treatment via a percutaneous approach using the DISKOM device (DISKOM percutaneous discectomy probe, Biopsybell, Mirandola, Italy). Indications, complications and various methods of use are described in relation to the different levels of the spine to be treated.